Synthesis and photovoltaic properties of organic photosensitizer using D-π-D type 4, 5-diazafluorene ligand and derivatives for efficient dye-sensitized solar cell - Cebeci, Caner; Kilicarslan, Fatma Aytan; Gurbuz, Osman; Firat, Yildiray; Okutan, Mustafa; Erden, Ibrahim (ELSEVIER SCI LTD, 2016)
In this paper, we synthesized and characterized ligand and complexes (Zn and Ru) and studied photovoltaic properties for dye-sensitized solar cells (DSSC) of new substances substituted with 4,5-Diazafluorene groups. The structural of the compounds were determined by FTIR, UV-Vis Spectrometer, H NMR, MS spectroscopic data and elemental analysis. The photovoltaic and electrochemical properties of these compounds were investigated and the applicability of these synthesized compounds in DSSCs as photosensitizers was studied. The photovoltaic cell efficiencies (PCE) of the devices were in the range of 0.580-2.015% under simulated AM 1.5 solar irradiation of 100 mW/cm(2), and the highest open-circuit voltage (V-oc) reached 0.34 V. When comparing the photovoltaic performance of the three DSSC devices, it seen that PCE assumes the following: DF-Ru > DF-Zn > DF. The PCE value of 2.015% (short photocurrent density, Jsc = 18.82 mA/cm(2), V-oc = 0.34 V, and fill factor, FF = 0.315) was obtained with a DSSC based on DF-Ru under AM irradiation (100 mW/cm(2)). DSSC based on DF-Zn produced efficiency of 1.430% whereas DSSC based DF exhibited the device performance with efficiency of 0.580% under illumination. These results suggest that DF-Zn and DF-Ru complexes displayed better photovoltaic activity than pure DF under visible light irradiation. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Dye-sensitized solar cell; Optical spectra; 4,5-Diazafluorene; Photovoltaic; Zinc and ruthenium complex; PERFORMANCE; COMPLEXES; BRIDGE; Chemistry; Engineering; Materials Science